Radio-Optically- and Thermally Stimulated Luminescence of Zn(BO2)2:Tb3+ exposed to Ionizing Radiation - Cruz Zaragoza, Epifanio (2017)
The optical absorption of zinc tetraborate at different concentrations of the terbium impurity (0, 0.5, 1, 2, 4, 8 mol%) was analyzed. Theradioluminescence (RL) emission spectra was obtained after beta irradiation of a 90Sr/90Y source. The RL spectrum showed the characteristics bands ofTb3+ with two main emissions at 489 nm and 546 nm which corresponding to the5D4 →7F6 and 5D4 →7F5 transitions respectively in this ion. The OSL and TLcharacteristics have been analyzed. The stimulation blue light (497 nm) of a diode laser at 500 mA was used to bleach the thermoluminescent (TL) signalsobtained with 5Gy of 60Co source. The two main glow peaks (79 and 161 °C) are sensitives under 497 nm stimulation, and they were shifted to highertemperature values and faded their TL intensities. Similar behavior of TL glow curves before and after OSL stimulation with blue light was observed whenthe samples were exposed to 30 Gy gamma dose of 137Cs irradiator. The OSL signal response was linear with the dose range of 1-10 Gy and increased theirresponse up to 200 Gy gamma dose. The OSL shows a bleaching sensitive shallow traps and diminishing the intensity of the TL glow curves remaining acomplex traps distribution. The RL, TL and OSL properties were investigated in Zn(BO2)2:Tb3+ phosphor.